Growth, mortality parameters and exploitation of the swimming crab Portunus trituberculatus (Miers, 1876) in the East China Sea - Kai, Zhu; Zhenhua, Li; Yongdong, Zhou; Kaida, Xu; Wenbin, Zhu; Zhongming, Wang (Indian Journal of Fisheries, 2021)
Based on the samples from bottom trawls collected during March to October 2020 in the East China Sea, growth parameters, mortality rate and recruitment pattern of the swimming crab, Portunus trituberculatus (Miers, 1876), were estimated using FiSAT II software. Parameters of the von Bertalanffy equation obtained by ELEFAN I for males and males respectively were: growth coefficient (k) -0.99 and 1.01, theoretical maximum carapace width (Lâˆž) - 22.58 and 21.53 cm and theoretical age at length 0 (t 0 ) -0.1738 and -0.15785. Mortality parameters estimated by the length onverted catch curve analysis for males and females were: total mortality (Z) -4.26 and 4.65, natural mortality (M) -1.643 and 1.784 and fishing mortality (F) -2.617 and 2.866, for females and males, respectively. The stock recruitment showed a bimodal pattern, in which the main peak was from July to October and the second peak in February and March. The exploitation rates arrived at were 0.61 and 0.62 for females and males respectively, while the exploitation maximum (Emax) obtained were 0.63 and 0.61 in females and males respectively. The results showed that, female swimming crabs in the East China Sea grow faster and reach larger carapace width than males and the current exploitation rate is very high and close to the value for maximum yield, indicating overfishing. Keywords: Biological parameters, East China Sea, Growth, Mortality, Portunus trituberculatus